2019
DOI: 10.18203/2349-3291.ijcp20190547
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on cardiac changes (electrocardiographic, enzymatic and echocardiographic) in birth asphyxiated neonates admitted in tertiary care centre

Abstract: Background: Reduced myocardial performance and cardiac output following perinatal asphyxia may significantly complicate perinatal management and may contribute to increased end-organ damage and mortality. Hence the present study was done with the aim to assess the usefulness of echocardiography, electrocardiography (ECG), and cardiac enzymes in evaluating myocardial damage in perinatal asphyxia neonates and to assess their correlation with different stages of hypoxic-ischemic encephalopathy (HIE) and outcome.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…We showed that newborns with the worst echo findings had a fatal outcome, as was previously demonstrated [25]. We showed that TRPG had a significant impact on the survival rate, with values of 45.5 mmHg on the 1 st day (sensitivity 100%, specificity 100%) and 39 mmHg on the 3 rd day (sensitivity 80%, specificity 100%).…”
Section: Discussionsupporting
confidence: 77%
“…We showed that newborns with the worst echo findings had a fatal outcome, as was previously demonstrated [25]. We showed that TRPG had a significant impact on the survival rate, with values of 45.5 mmHg on the 1 st day (sensitivity 100%, specificity 100%) and 39 mmHg on the 3 rd day (sensitivity 80%, specificity 100%).…”
Section: Discussionsupporting
confidence: 77%
“…Shadique and Sailavasan; Saira et al, and Mandal et al, support our findings. 7 The enzyme levels showed a significant rise with severe birth asphyxia, which indicates significant myocardial ischemia in cases of severe birth asphyxia. ECG abnormalities were seen in almost 2-15% of cases in our study, which is lower than the study done by Rajakumar et al,(73.33%) and Agrwal et al,(76.77%).…”
Section: Discussionmentioning
confidence: 98%
“…This was in contrary to the studies by Shadique AM et al, where statistical significance was not seen, however studies by Lakshmanan et al, showed statistical significance of APGAR scores with stages of perinatal asphyxia. 26,27 This difference could probably be attributed to the difference of the number of newborns enrolled in the studies with severe asphyxia.…”
Section: Discussionmentioning
confidence: 99%